State-of-the-Art of High-Power Gyro-Devices. Update of Experimental Results 2021 - Thumm, Manfred (KIT Scientific Reports, 2021)
This report presents an update of the experimental achievements published in the review "State- of-the-Art of High-Power Gyro-Devices and Free Electron Masers", Journal of Infrared, Millime-ter, and Terahertz Waves, 41, No. 1, pp 1-140 (2020) related to the development of gyro-devices (Tables 2-34). Emphasis is on high-power gyrotron oscillators for long-pulse or continuous wave (CW) operation and pulsed gyrotrons for any applications.